Play in Finnish kindergartens : an exploratory study on the pedagogical practices and opinions of teachers and nurses - Ravaglia, Martina (2021)
Play is a key aspect of pedagogical practice in Finnish kindergartens, and ECEC practitioners are advised to appropriately guide or take part in playful activities, supporting children’s learning and natural curiosity. This study explores the phenomenon of play from the perspectives of teachers and nurses, as well as from the observations made during the researcher’s internship in a Finnish day-care centre. The participants of this study, six educators, whose working experience in Finnish kindergartens ranged from six months to ten years, filled out a self-reflective open-ended questionnaire in English about their beliefs and experiences on play and playful learning, with children aged three to six. Questionnaire answers and observation notes were examined using inductive Content Analysis. Results illustrate that pedagogical practice draws on active observation of children’s interests and needs and that ECEC practitioners make appropriate use of the environment and of teacher-guided play, to encourage children’s autonomy and initiative-taking. Moreover, participation in children’s play takes shape both as a voluntary intervention of the educator and as a request from children themselves. Finally, educators report considering play as a vehicle for learning, which encompasses all the areas of development, and arranging elaborate and fun playful learning activities, making the most of music and P.E. time. Results are consistent with previous literature findings analysing ECEC play-based pedagogies and intend to contribute to the existing theory on play with concrete instances, and to support ECEC practitioners’ everyday work.